THE EMERGENCE AND PROSPECTS FOR THE DEVELOPMENT OF BLOCKCHAIN TECHNOLOGIES IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Blockchain is a technology for processing, storing information and identifying of customers. Literally from English blockchain (blockchain) is translated as "Chain of blocks", and the technology itself was proposed in 2008 by Satoshi Nakamato (pseudonym of a person or group of people).The purpose of writing the article is to study and identify regularity and prospects for the application of progressive and practical information technologies in Ukraine and the world.The main features of blockchain technology:transparency - the blockchain stores data on all conducted operations throughout the history of the system (cryptocurrency)stability - you can't remove or replace information "behindhand", but only to implement a new agreementindependence - information is not stored on one central server, but on many computers of network participants.The operation of the blockchain can be compared with Torrent - the functioning of the system takes place in P2P mode (peer to peer - computer network, where all participants are equal). When we download a movie from the tracker, the central server is not used. All transactions are directly conducted between network participants. And they are carried out due to the fact that their computers are connected to one network - a blockchain.The widespread popularity and spread of blockchain technology is in demand to develop applications that work on the principles of this innovation, and relevant IT professionals. The market is even short of blockchain system developers in general, and especially those who have the skills to work with distributed databases.However, the blockchain system also has its drawbacks. For example, because the data are stored on all computers of participants, for registration of operations it is required processing large amounts of data, which causes increased demands on the computer and to Internet speed for network members. This fact also causes great energy consumption for maintenance of operations in the system, for example, according to economists' calculations for next year's electricity costs bitcoin services in the world will be comparable to annual energy consumption of a small country such as Denmark.Blockchain technology is not regulated by any legislation that causes additional legal risks, for example, if your account is hacked by hackers, so this area of technology processing and storage of information requires proper legislative and legal regulation both at the level of Ukraine and at worldwide.Summing up, we can say that:Blockchain is a technology that allows you to implement the most sustainable digital registers in the world.The number of successful startups in this field is ten times greater than in traditional IT.Public blockchain databases are not controlled by any organization or state.Recording in public blockchains is available to absolutely everyone. You need only have minor technical training.Using of Blockchain very often eliminates the need in intermediaries.States consider and adopt legislative initiatives in this direction.The principles underlying the technology are extremely strong, which is the key to further development.
Keywords: cryptocurrency, virtualbank, blockchain technology, internet banking, financial technologies.